PENGGUNAAN PERAGKAT LUNAK ILEGAL COMPUTER BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Kusuma Heryawan, Hangga (Universitas Wiralodra, 2017)
Many of the problems concerning illegal software that occur in Indonesia, installing windows programs circulating in the community do not pay attention to the authenticity of devices installed in the computer, so the software installed on the computer is not genuine. The use of illegal software becomes a common habit in the community, because the nominal factor is cheaper and affordable. Because of the convenience factor, people do not know the rules governing the use of illegal software, which is detrimental to the creator.